2016
DOI: 10.1038/ncomms13197
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer transcriptomic analysis associates long non-coding RNAs with key mutational driver events

Abstract: Thousands of long non-coding RNAs (lncRNAs) lie interspersed with coding genes across the genome, and a small subset has been implicated as downstream effectors in oncogenic pathways. Here we make use of transcriptome and exome sequencing data from thousands of tumours across 19 cancer types, to identify lncRNAs that are induced or repressed in relation to somatic mutations in key oncogenic driver genes. Our screen confirms known coding and non-coding effectors and also associates many new lncRNAs to relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 76 publications
0
43
1
Order By: Relevance
“…Of note, Ashouri et al recently identified a lncRNA RP11‐115D19.1 (we named it as TRINGS), which is negatively associated with p53 mutation, and exhibited reduced transcription in p53 null cells as compared to p53 wild‐type cells. In addition, expression for this lncRNA (TRINGS) was similarly seen to be reduced in p53‐mutated tumor samples (Ashouri et al , ).…”
Section: Discussionmentioning
confidence: 98%
“…Of note, Ashouri et al recently identified a lncRNA RP11‐115D19.1 (we named it as TRINGS), which is negatively associated with p53 mutation, and exhibited reduced transcription in p53 null cells as compared to p53 wild‐type cells. In addition, expression for this lncRNA (TRINGS) was similarly seen to be reduced in p53‐mutated tumor samples (Ashouri et al , ).…”
Section: Discussionmentioning
confidence: 98%
“…None of the HIF genes were differentially expressed, maybe because the activation of HIF-1 only lasts for a period after cerebral ischemia 43 . A significant downregulated lncRNA in brain-0 and brain-1, RP11-284F21.9 ( Fig.XC), is antisense to BCAN 44 . BCAN (Brevican) encodes a member of proteoglycans that is specifically expressed in CNS, maintaining the extracellular environment of mature brain 45 .…”
Section: Differential Expression Analysis Of Brain Transcriptomesmentioning
confidence: 99%
“…RNAseq data and copy number data were downloaded from TCGA and 780 processed as described previously (Ashouri et al 2016). Briefly, RNAseq data 781 were aligned to the human hg19 assembly and quantified using GENCODE 782 (v19) annotated HTSeq-counts and FPKM normalizations.…”
Section: Tcga Data Analysis 779mentioning
confidence: 99%